Self-assembled curcumin-PAH nanoplex with enhanced solubility - Zhang, Jie (2014)
Self-assembled drug-polyelectrolyte complexation is a novel formulation of a nanoscale amorphous drug from its poorly soluble crystalline form, resulting in greater solubility and enhanced bioavailability of the drug. Nanoscale amorphous drug is formed by dispersing the ionised drug particles onto an oppositely charged polyelectrolyte (PE). The drug-PE complex is held together by strong electrostatic interaction. [2nd Award]